Influence of Tempering and Cryogenic Treatment on Retained Austenite and Residual Stresses in Carbonitrided 18CrNiMo7-6 Low Alloy Steel - Katemi, Richard J.; Epp, Jérémy (Tanzania Journal of Engineering and Technology, 2019)
This work investigated the influence of tempering conditions coupled with cryogenic treatment on thermal stabilization of retained austenite and residual stress distributions in carbonitrided 18CrNiMo76 low alloy steel samples. The carbonitriding conditions were set to enable attaining surface carbon and nitrogen content of 0.87 and 0.34 mass.-percent respectively. After carbonitriding, some of the samples were subjected to varying tempering conditions followed by cryogenic treatment at -120 °C using nitrogen gas. Analysis of both retained austenite and residual stresses was conducted using X-ray diffraction. In the as-quenched state, carbonitrided samples contained 52 mass.-percent. Samples that were directly subjected to the cryogenic treatment after quenching retained only about 20 mass.-percent of austenite. Samples subjected to variant tempering conditions coupled with cryogenic treatment retained at least 30 masses.-percent of austenite. A thermal stabilization of retained austenite which increases with increasing temperature was identified. On tempering at 240 °C for 14 hours retained austenite becomes unstable and decomposes to bainite leading to the low initial amount of retained austenite before cryogenic treatment. It can be concluded that the tempering process coupled with cryogenic treatment leads to an increasing hardness, to higher compressive residual stresses as well as to a shift of the location of maximum compressive residual stress toward the surface. Keywords: Carbonitriding, cryogenic, residual stress, residual stress, tempering, XRD.